The correlation between airborne pollen and asthma in children: a systematic review and meta-analysis - Wang, Xiaoya; Liu, Bo; Yang, Yujie; Li, Jimin; Tian, Ziyan; He, Jinwei; Li, Yuanxia (Frontiers in Pediatrics, 2025)
BackgroundChildhood asthma is a prevalent chronic respiratory disease globally. Airborne pollen is a known environmental trigger, but the impact of different pollen types on pediatric asthma remains unclear. Seasonal and geographic pollen variations, influenced by climate change, may affect asthma patterns. A comprehensive review is needed to clarify these associations and guide prevention strategies.MethodsRelevant literature on the association between airborne pollen and asthma in children was retrieved from CNKI, Wanfang Data, VIP, CBM, Web of Science, PubMed, Cochrane and Embase at home and abroad from the establishment of the database to March 1, 2025. EndNote X8 and Excel 2021 were used for data management and screening, while Stata 15 was used for statistical analysis.ResultsA total of 9 articles were included in this meta-analysis, from 2007 to 2024, with a total sample size of 87,270 children. The pooled analysis showed that airborne pollen exposure was significantly associated with the risk of childhood asthma (OR = 1.23, 95% CI: 1.13–1.33, P < 0.001). Subgroup analysis showed that the combined effect size of tree pollen exposure was OR = 1.56 (95% CI: 0.99–2.12, P < 0.001), and the effect size of grass and weed pollen exposure was OR = 1.06 (95% CI: 1.01–1.12, P < 0.001). The comprehensive effect size of literature considering air pollutants and climatic factors was OR = 1.35 (95% CI: 1.20–1.50, P = 0.034), while literature not considering these factors was OR = 1.08 (95% CI: 1.06–1.10, P = 0.156). Age subgroup analysis showed that the effect size for preschool children was OR = 1.31 (95% CI: 0.53–2.09, P = 0.156), and for school-age children was OR = 1.52 (95% CI: 1.32–1.73, P = 0.298). Sensitivity analysis and Egger's test showed no significant publication bias.ConclusionAirborne pollen is a notable risk factor for childhood asthma, and tree pollen exposure may be more dangerous than grass and weed pollen exposure. When atmospheric pollutants and meteorological conditions are considered, the association between airborne pollen and childhood asthma is more pronounced. The evidence is insufficient to support a significant age-related difference between pollen and asthma.